Guiding the Treatment of Hidradenitis Suppurativa: A Role for Therapeutic Drug Monitoring - Vanhoutte, Charlotte; Hillary, Tom; Laethem, An Van (Archives of Clinical and Medical Case Reports, 2022)
Background: Although the precise pathophysiology of Hidradenitis Suppurativa (HS) is yet to be elucidated, involvement of various cytokines has been proposed. Accordingly, the use of biologics has been introduced in the armamentarium and adalimumab is currently the only registered biologic for this indiciation. However, case series for IL-12/23 and IL 23-inhibitors are emerging. In case of therapeutic failure or loss of response to a biological, therapy is often blindly adapted, whereas Therapeutic Drug Monitoring (TDM) might assist in a personalized approach to optimize treatment. TDM has shown to be effective in other inflammatory diseases with overlapping pathogenesis. Methods: We present a case of HS with waning response to first adalimumab and then guselkumab for both of which TDM was performed. Research of the literature was conducted. Results: Our patient showed a waning clinical response that was paralleled by a drop in the Trough Levels (TL), first of adalimumab, then of guselkumab. Literature search showed only scarce data on TDM in HS patients. Conclusion: Future research is warranted to determine optimal serum TL for therapeutic efficacy of the biologicals in the treatment of HS.